Preliminary Study Of Desiccant Cooling System Under Algerian Climates - N. Hatraf; N. Moummi (Zenodo, 2016)
The interest in air conditioning using renewable energies is increasing. The thermal energy produced from the solar energy can be converted to useful cooling and heating through the thermochemical or thermophysical processes by using thermally activated energy conversion systems. The ambient air contains so much water that very high dehumidification rates are required. For a continuous dehumidification of the process air, the water adsorbed on the desiccant material has to be removed, which is done by allowing hot air to flow through the desiccant material (regeneration). A solid desiccant cooling system transfers moisture from the inlet air to the silica gel by using two processes: Absorption process and the regeneration process. The main aim of this paper is to study how the dehumidification rate, the generation temperature and many other factors influence the efficiency of a solid desiccant system by using TRNSYS software. The results show that the desiccant system could be used to decrease the humidity rate of the entering air. : {"references": ["H. Ren, W. Gao, W. Zhou, K. Nakagam, Multi-criteria evaluation for the optimal adoption of distributed residential energy systems in Japan, Energy Policy, Volume 37, Issue 12, 2009, Pages 5484-5493.", "G. Panaras, E. Mathioulakis, V. Belessiotis, N. Kyriakis. Theoretical and experimental investigation of the performance of a desiccant air conditioning system. Renewable Energy2010:35:1368-1375.", "N. Wadkar, A. Patil, A. Kolhe. Energy Performance Evaluation of Desiccant Based Air Conditioning Test Rig. International Journal of Innovative Research in Science Engineering and Technology2014:3:1-8", "Toftum J, Anette J, Fanger PO. Upper limits for indoor air humidity to avoid uncomfortable humid skin. Energy Build1998:28:1-13.", "Reinikainen LM, Jaakkola JJK. Significance of humidity and temperature on skin and upper airway symptoms. Indoor Air 2003; 13:344\u201352", "Bornehag CG, Blomquist G, Gyntelberg F, et al. Nordic interdisciplinary review of the scientific evidence on associations between exposure to 'Dampness' in buildings and health effects. Indoor Air 2001; 13:72\u201386.", "Bornehag CG, Sundell J, Bonini S. Dampness in buildings as a risk factor for health effects, Euroexpo: a multidisciplinary review of the literature (1998\u20132000) on dampness and mite exposure in buildings and health effects. Indoor Air 2004; 14:243\u201357.", "Hemant. P, Hindoliya. D.A, \"Performance of a solid desiccant based evaporative cooling system in warm and humid climatic zone of India.", "Giovanni Angrisani. Experimental and Simulative Analysis of a Microtrigeneration System Based on an Air Handling Unit with Desiccant Wheel. PHD Thesis Universit\u00e9 de Napoli."]}